Prototipe Sistem Monitoring Jaringan Dan Otomasi Bandwidth Manager Dengan Visualisasi Grafana Pada Lingkungan Virtual - Ridho Affandi; Dedy Kiswanto; Syti Salwaa Nafiisah; Shaqila Rahmayani (PPPM Institut Teknologi Pagar Alam, 2026)
The increasing complexity of information technology–based services has led to a growing demand for reliable and efficient network management. Network performance monitoring and bandwidth allocation control are critical aspects in maintaining network stability, availability, and quality of service. This paper presents the development of a network monitoring system prototype integrated with an automated bandwidth management mechanism in a virtualized environment. The system is designed to collect network performance data in real time, automatically manage traffic priorities, and present network information through clear and informative visualizations. A virtual environment is utilized to provide flexibility, resource efficiency, and ease of system testing. The prototype results indicate that the system enhances network visibility, supports more effective bandwidth management, and enables structured traffic control. This prototype is expected to serve as an initial solution for network management and as a foundation for further development of network monitoring and automation systems.